2008
DOI: 10.5194/acp-8-2421-2008
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ACE-FTS v2.2 methane profiles from the upper troposphere to the lower mesosphere

Abstract: Abstract. The ACE-FTS (Atmospheric Chemistry Experiment -Fourier Transform Spectrometer) solar occultation instrument that was launched onboard the Canadian SCISAT-1 satellite in August 2003 is measuring vertical profiles from the upper troposphere to the lower mesosphere for a large number of atmospheric constituents. Methane is one of the key species. The version v2.2 data of the ACE-FTS CH 4 data have been compared to correlative satellite, balloonborne and ground-based Fourier transform infrared remote sen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 40 publications
4
73
0
Order By: Relevance
“…We compared MIPAS profiles to HALOE data version v19. This version has already been compared to ACE-FTS v2.2 profiles by De Mazière et al (2008), where HALOE data were shown to have mixing ratios about 5-10 % lower than ACE-FTS. Waymark et al (2013) found the CH 4 ACE-FTS version 3.0 mixing ratios to be reduced at some altitudes compared to version 2.2.…”
Section: Haloementioning
confidence: 99%
See 1 more Smart Citation
“…We compared MIPAS profiles to HALOE data version v19. This version has already been compared to ACE-FTS v2.2 profiles by De Mazière et al (2008), where HALOE data were shown to have mixing ratios about 5-10 % lower than ACE-FTS. Waymark et al (2013) found the CH 4 ACE-FTS version 3.0 mixing ratios to be reduced at some altitudes compared to version 2.2.…”
Section: Haloementioning
confidence: 99%
“…Waymark et al (2013) found the CH 4 ACE-FTS version 3.0 mixing ratios to be reduced at some altitudes compared to version 2.2. And since the version 3.5 research CH 4 data have even lower mixing ratios than version 3.0, the difference between HALOE v19 and the latest ACE-FTS version (3.5 research) should be smaller than those in the earlier versions found by De Mazière et al (2008). The typical vertical resolution of the profiles is given as 3-5 km ).…”
Section: Haloementioning
confidence: 99%
“…These include balloons , TCCON stratospheric retrievals (Saad et al, 2014), and satellite observations by solar occultation and in the limb (de Mazière et al, 2008;von Clarmann et al, 2009;Minschwaner and Manney, 2014). Bergamaschi et al (2013) presented a detailed evaluation of their CTM with balloon observations as a prelude to inversion of SCIAMACHY data, and this led them to limit their inversion to the 50 • S-50 • N latitudinal range where model bias was small.…”
Section: Stratospheric Methanementioning
confidence: 99%
“…Tropospheric columns have been shown to represent the magnitude and seasonality of in situ measurements (Saad et al, 2014;Washenfelder et al, 2003;Wang et al, 2014). The tropospheric CH 4 column-averaged DMFs (X t CH 4 ) are derived by the hydrogen fluoride (HF) proxy method described in Saad et al (2014), which uses the relationship between CH 4 and HF in the stratosphere, derived from ACE-FTS satellite measurements (Bernath, 2005;De Mazière et al, 2008;Mahieu et al, 2008;Waymark et al, 2014), to calculate and remove the stratospheric contribution to X CH 4 . The X t CH 4 used in this analysis have been processed consistently with the GGG2014 TCCON products, with air-mass dependence and calibration factors calculated for and applied to X t CH 4 .…”
Section: Tropospheric Methane Columnsmentioning
confidence: 99%